The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/2158244015589588
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Mathematics Manipulatives Effective? Lessons From Cognitive Science and Montessori Education

Abstract: Manipulatives are ubiquitous in early childhood classrooms; yet, findings regarding their efficacy for learning mathematics concepts are inconsistent. In this article, we present four general principles that have emerged from cognitive science about ways to ensure that manipulatives promote learning when used with young children. We also describe how Montessori instruction offers a concrete example of the application of these principles in practice, which may, in turn, explain the high levels of mathematics ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 36 publications
(46 reference statements)
0
35
0
8
Order By: Relevance
“…Further, a recent study found no differences between East Asian and American kindergartners' use of base-10 representations in children with less than one year of formal instruction (Vasilyeva et al, 2015), despite these differences being well documented at the end of first grade, after more than one year of formal instruction (e.g., Miura et al, 1993). The Montessori mathematics curriculum places great emphasis on base 10 and place value using a series of materials (e.g., golden beads, stamp game, bead frames) that highlight these concepts, even with children as young as 3 years (Laski, Jor'dan, Daoust, & Murray, 2015;Lillard, 2005;Montessori & Simmonds, 1917). Thus, it seemed plausible that differences in young children's understanding of base 10 and place value may exist based on whether they had experienced Montessori mathematics instruction between the ages of 3 and 6 years.…”
Section: Base-10 and Place-value Understandingmentioning
confidence: 99%
“…Further, a recent study found no differences between East Asian and American kindergartners' use of base-10 representations in children with less than one year of formal instruction (Vasilyeva et al, 2015), despite these differences being well documented at the end of first grade, after more than one year of formal instruction (e.g., Miura et al, 1993). The Montessori mathematics curriculum places great emphasis on base 10 and place value using a series of materials (e.g., golden beads, stamp game, bead frames) that highlight these concepts, even with children as young as 3 years (Laski, Jor'dan, Daoust, & Murray, 2015;Lillard, 2005;Montessori & Simmonds, 1917). Thus, it seemed plausible that differences in young children's understanding of base 10 and place value may exist based on whether they had experienced Montessori mathematics instruction between the ages of 3 and 6 years.…”
Section: Base-10 and Place-value Understandingmentioning
confidence: 99%
“…McNeil and Jarvin (2007) weigh up both sides of the debate on the effective use of mathematical manipulatives, though the counterevidence they provide focuses mainly on the "cognitive resources" of children and so is harder to reconcile with the abilities of adults in higher education. We believe that other recommendations, such as principles (c) and (d) described by Laski, Jor'dan, Daoust, and Murray (2015), are in line with the use of manipulatives within the scope of this module, with their other principles again focussing on the cognitive capabilities of children rather than adults. If used in the right way, physical objects can be used to represent abstract ideas in physical form to "help students deeply understand the math they are learning and needing to apply to our everyday life" (Furner and Worrell, 2007).…”
Section: Introductionmentioning
confidence: 63%
“…This relating activities could help students have meaningful understanding of the place values and the operations. The understanding could help students improve ability to solve problems, creative thinking, and learning outcomes [12] [13].…”
Section: Discussionmentioning
confidence: 99%